DEVELOPMENT OF SMART PARKING SYSTEM DESIGN AT PT. SI - Asrar, Leni Devera (Jurnal Kajian Teknik Elektro, 2025)
Parking area problems generally still rely on traditional systems, while the automatic smart parking system utilizes RFID (Radio Frequency Identification) technology to manage vehicle access in and out of the parking area. This smart parking system is designed using RFID integrated with the Arduino Uno microcontroller, and system programming is carried out using the Arduino IDE (Integrated Development Environment) software. A survey of parking facilities at PT. SI conducted on 50 employees showed that 82.80% of them did not get a parking space and had to park their vehicles elsewhere because the parking area was full and it was difficult to find an empty parking lot. In addition, 67.20% of respondents stated that the parking area was poorly lit. This article discusses the design of an RFID-based smart parking system implemented using Arduino Uno, which makes it easier for drivers to find available parking spaces with the help of LED lights. The Research & Development method is used in this study to produce and test the effectiveness of the product prototype. The results of the study show that the prototype of the RFID-based smart parking system and RFID cards has been successfully developed, with information on parking availability displayed on the LCD screen. This prototype is also equipped with LED lights that make it easier for drivers to find empty parking areas. Furthermore, a more sophisticated RFID system is being developed to improve RFID reading response, as well as being equipped with CCTV and other security support sensors to improve the security of the smart parking system.